High Frequency of CYP2A6*4, CYP2A6*7, and CYP2A6*9 Alleles Detected Among Patients with Type 2 Diabetic: Genetic Study in The Private Hospital in Yogyakarta - Christine Patramurti; Dita Maria Virginia; Fenty Fenty; Christianus Heru Setiawan; Jeffry Julianus; Phebe Hendra; Nicholas Adi Perdana Susanto (Sanata Dharma University, 2022)
Smoking is a risk factor for type 2 diabetic (T2DM), since the nicotine in cigarettes can cause insulin resistance and increase lipolysis. Both of these can worsen the condition of patients with T2DM and increase treatment failure. Nicotine is metabolized to cotinine by the CYP2A6 enzyme encoded by the CYP2A6 gene. This gene is highly polymorphic, with several inactive alleles, which are CYP2A6 *4, CYP2A6 *7, and CYP2A6 *9. Someone who has an inactive gene will experience being a slow or poor metabolizer. Therefore, the nicotine metabolism will decrease, nicotine blood levels will increase, causing therapy failure among patients with T2DM. This study aims to determine the distribution of CYP2A6*4, CYP2A6*7, and CYP2A6*9 among patients with T2DM who have been routinely treated using oral antidiabetics. We also investigated whether HbA1c levels is a predictor for the success of the treatment. This observational study was conducted with a cross-sectional design. Polymerase chain reaction was used to analyze the three inactive alleles with specific primers. Based on our study, there is a high frequency of the inactive alleles, i.e., CYP2A6*4, CYP2A6*7, and CYP2A6*9, among the patients with T2DM. The presence of these inactive alleles will worsen and reduce the effectiveness of the therapy. Smoking cessation programs are needed to increase the effectiveness of the anti-diabetic therapy.